Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

Basal area loss from fire using field-calibrated remote sensing refines western US fire severity measurements - Sara Winsemius; Yufang Jin; Hugh D. Safford; Michelle C. Agne; Robert A. Andrus; C. Alina Cansler; Anthony C. Caprio; W. Wallace Covington; Joseph E. Crouse; Calvin Farris; Peter Z. Fulé; Brian J. Harvey; et al. (Remote Sensing of Environment, 2026)

Productivity dynamics of agroecosystems under prevailing and alternative management practices across the United States - Omodara E. Obisesan; Adam P. Schreiner-McGraw; Jeffrey D. Wood; Jiquan Chen; Joshua D. Gamble; Timothy J. Griffis; Christina M. Helseth; Makki Khorchani; Claire L. Phillips; Kathryne Rumora; Russell L. Scott; Xiangmin Sun; et al. (Agricultural and Forest Meteorology, 2026)

Marine Isotope Stage 4 glaciation in northern England, UK: Evidence from Victoria Cave, North Yorkshire - Tom C. Lord; Peter Wilson; Joyce Lundberg; Adrian P. Palmer; Matt W. Telfer; Rhiannon E. Stevens; Phillip J. Murphy; Mark Lewis (Journal of Quaternary Science, 2026)
Victoria Cave, north Yorkshire, England, contains a long sequence of Pleistocene clastic sediments and calcite flowstones. Earlier work, using U–Th dating, established that the flowstone units formed in interglacial stages corresponding to Marine Isotope Stages (MIS) 13, 11, 9, 7 and 5. The intervening laminated sediments were therefore assigned to glacial stages (MIS 12, 10, 6 and 2) and regarded as rhythmites that settled from ponded glacial meltwater in the cave. Victoria Cave is a rare instance of cave rhythmites that formed over a number of glacial–interglacial cycles. The macro‐ and micromorphologies of the rhythmites support the above interpretation, and the mineralogy demonstrates that the sediments probably derive from rock types within the local area. An OSL age of 66 ± 8.4 ka from the uppermost unit of the rhythmites and two 14 C ages of 46.1–54.9 cal. ka BP and 48.9–>55.0 cal. ka BP, for horse and reindeer, respectively, from the overlying Bone‐bearing Cave Earth provide a new chronology for these Late Pleistocene sediments. Together, these results indicate that the youngest rhythmites in Victoria Cave formed during MIS 4 and not MIS 2 as previously assumed. This provides strong support for more widespread glaciation in northern England in MIS 4 (~71–59 ka) than has previously been recognised. The MIS 4 rhythmites represent the most tightly constrained cave rhythmites in Britain and the first terrestrial‐based evidence from this area for glaciation at that time.

A high-resolution record of early rift development and tectonic, sedimentary and environmental conditions in an active rift basin: IODP MSP drilling in the Corinth Rift, Greece (Expedition 381) - Lisa C. McNeill; Donna J. Shillington; Jeanine Ash; Gareth D.O. Carter; Richard E.Ll. Collier; Aleksandra Cvetkoska; Paula Diz; Mai-Linh Doan; Jeremy D. Everest; Natacha Fabregas; Eugenia Fatourou; Mary Ford; et al. (Marine Geology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Biofilm Responses to Experimental Nutrient Enrichment of Forest Streams: Light and Nutrients Interact to Increase Biomass, and Phosphorus Alters Stoichiometry - Phillip M. Bumpers; Jonathan P. Benstead; Vladislav Gulis; John S. Kominoski; John C. Maerz; David W. P. Manning; Seth J. Wenger; Amy D. Rosemond (Ecosystems, 2025)
Nutrient enrichment of aquatic ecosystems typically results in increased algal biomass, but the response magnitude is predicted to be attenuated in light-limited ecosystems. We tested the effects of experimental nutrient enrichment in small, highly shaded forest streams and compared responses of biofilm biomass and biofilm stoichiometry, which may be less sensitive to light. After one year of pre-treatment data collection, we enriched five streams continuously for 2 years with different ratios of nitrogen (N) and phosphorus (P), which allowed us to test the relative effect of N and P on two measures of biomass—chlorophyll a (Chl a ) and ash-free dry mass (AFDM)—and on biofilm stoichiometry (C:N, C:P, and N:P) monthly. Biomass increased in response to light and both nutrients; annual average Chl a increased 9.28 × and AFDM increased 1.13 × Biofilm stoichiometry was driven largely by streamwater P concentration, with greatest effects of experimental enrichments on C:P (0.58 ×) and N:P (0.79 ×). Biofilm C:P and N:P increased across the streamwater N:P gradient. Light had only weak effects on biofilm C:P and N:P ratios, suggesting biofilm stoichiometry could function as a useful indicator of nutrient pollution when light limitation might otherwise dampen changes in biomass. The lowest C:N and C:P ratios were associated with increased Chl a :AFDM ratios, indicating increased autotrophic contributions were associated with greater N and P content. Even in low-light environments, we detected relatively large responses of algae-containing biofilms to N and P enrichment, consistent with previously reported effects of experimental nutrient addition, including primary and secondary consumer growth and production.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Resource quantity and quality co‐limit consumer production in forest streams - Lee M. Demi; Phillip M. Bumpers; Wyatt F. Cross; Susan L. Eggert; John S. Kominoski; David W. P. Manning; Amy D. Rosemond; J. Bruce Wallace; Seth J. Wenger; Jonathan P. Benstead (Ecology, 2025)
Ecological theory predicts that consumers should be co‐limited by resource quantity and quality, given widespread consumer‐resource nutritional imbalances. We used 25 estimates of annual community secondary production (ACSP) of stream macroinvertebrates to assess the relative roles of basal resource quantity (leaf litter standing stock [LLSS]) and quality (% nitrogen and % phosphorus of leaf litter) in modulating patterns of production in forest streams. We also tested the effects of hypothesized indirect drivers (stream discharge and inorganic nutrient concentrations) on basal resource quality and quantity and secondary production. In the top model for ACSP, LLSS, and %P together explained 59% of its variation, providing strong evidence of co‐limitation by both resource quantity and quality. Mean annual stream discharge and stream water P concentration explained 75% and 43% of variation in LLSS and %P, respectively. Together, stream discharge and stream water P concentration explained 77% of the variation in ACSP, demonstrating a critical link between hypothesized indirect and direct (basal resources) drivers and ACSP. Our results are the first to demonstrate co‐limitation of ACSP and highlight several mechanisms by which drivers of anthropogenic global change, such as altered precipitation (stream discharge) and eutrophication, influence the productivity of animal communities in stream ecosystems.

The applicability of regional red list assessments for soil invertebrates: first assessment of five native earthworm species in Canada - Helen R. P. Phillips; George G. Brown; Sam W. James; Jérôme Mathieu; John Warren Reynolds; Maheshi E. Dharmasiri; Claire L. Singer; Maria J. I. Briones; Heather C. Proctor; Erin K. Cameron (Biodiversity and Conservation, 2025)
Earthworms (Annelida: Clitellata: Crassiclitellata) are prominent members of the soil community, important to many ecosystem functions. Despite this, and like many other soil invertebrates, they are rarely considered in conservation assessments, including the International Union for Conservation of Nature (IUCN) Red List assessments used to assess species’ extinction risk. To investigate the applicability of the IUCN Regional Red Listing protocol to soil invertebrates, we assessed the conservation status of five earthworm species native to Canada using this protocol and all available occurrence records. In Canada, no earthworm species have yet been assessed by the Committee on the Status of Endangered Wildlife in Canada (COSEWIC). Due to the lack of data on population sizes and their trends, all five species were assessed using their Extent of Occurrence (EOO) (Criterion B). One species was assessed as Vulnerable ( Arctiostrotus vancouverensis) , two were assessed in non-threatened categories ( A. perrieri and Sparganophilus tamesis ), and two were assessed as Data Deficient ( A. fontinalis and Toutellus oregonensis ). For the majority, the main threats identified were the continuing loss of potential habitat due to land conversion and resource exploitation, as well as the effects of climate change. Increasing the amount of data, including but not limited to distribution and habitat preferences, would make the assessment process easier and status decisions better supported. By undertaking regional assessments for five native earthworm species in Canada, we show that Regional Red List assessments are feasible for soil invertebrates.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Temporal concentrations of Quaternary ammonium compounds in wastewater treatment effluents during the COVID-19 pandemic, 2020–2021 - Michelle L. Hladik; Michael S. Gross; Gabrielle P. Black; Dana W. Kolpin; Jason R. Masoner; Patrick J. Phillips; Paul M. Bradley; Kelly L. Smalling (Chemosphere, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

In vitro screening of per- and polyfluorinated substances (PFAS) for interference with seven thyroid hormone system targets across nine assays - Sigmund J. Degitz; Jennifer H. Olker; Jeffery S. Denny; Philip P. Degoey; Phillip C. Hartig; Mary C. Cardon; Stephanie A. Eytcheson; Jonathan T. Haselman; Sally A. Mayasich; Michael W. Hornung (Toxicology in Vitro, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Environment and shipping drive environmental DNA beta‐diversity among commercial ports - Jose Andrés; Paul Czechowski; Erin Grey; Mandana Saebi; Kara Andres; Christopher Brown; Nitesh Chawla; James J. Corbett; Rein Brys; Phillip Cassey; Nancy Correa; Marty R. Deveney; et al. (Molecular Ecology, 2023)
The spread of nonindigenous species by shipping is a large and growing global problem that harms coastal ecosystems and economies and may blur coastal biogeographical patterns. This study coupled eukaryotic environmental DNA (eDNA) metabarcoding with dissimilarity regression to test the hypothesis that ship‐borne species spread homogenizes port communities. We first collected and metabarcoded water samples from ports in Europe, Asia, Australia and the Americas. We then calculated community dissimilarities between port pairs and tested for effects of environmental dissimilarity, biogeographical region and four alternative measures of ship‐borne species transport risk. We predicted that higher shipping between ports would decrease community dissimilarity, that the effect of shipping would be small compared to that of environment dissimilarity and shared biogeography, and that more complex shipping risk metrics (which account for ballast water and stepping‐stone spread) would perform better. Consistent with our hypotheses, community dissimilarities increased significantly with environmental dissimilarity and, to a lesser extent, decreased with ship‐borne species transport risks, particularly if the ports had similar environments and stepping‐stone risks were considered. Unexpectedly, we found no clear effect of shared biogeography, and that risk metrics incorporating estimates of ballast discharge did not offer more explanatory power than simpler traffic‐based risks. Overall, we found that shipping homogenizes eukaryotic communities between ports in predictable ways, which could inform improvements in invasive species policy and management. We demonstrated the usefulness of eDNA metabarcoding and dissimilarity regression for disentangling the drivers of large‐scale biodiversity patterns. We conclude by outlining logistical considerations and recommendations for future studies using this approach.

Antioxidants green tea extract and nordihydroguaiaretic acid confer species and strain-specific lifespan and health effects in Caenorhabditis nematodes - Stephen A. Banse; Christine A. Sedore; Erik Johnson; Anna L. Coleman-Hulbert; Brian Onken; David Hall; E. Grace Jackson; Phu Huynh; Anna C. Foulger; Suzhen Guo; Theo Garrett; Jian Xue; et al. (GeroScience, 2023)
The Caenorhabditis Intervention Testing Program (CITP) is an NIH-funded research consortium of investigators who conduct analyses at three independent sites to identify chemical interventions that reproducibly promote health and lifespan in a robust manner. The founding principle of the CITP is that compounds with positive effects across a genetically diverse panel of Caenorhabditis species and strains are likely engaging conserved biochemical pathways to exert their effects. As such, interventions that are broadly efficacious might be considered prominent compounds for translation for pre-clinical research and human clinical applications. Here, we report results generated using a recently streamlined pipeline approach for the evaluation of the effects of chemical compounds on lifespan and health. We studied five compounds previously shown to extend C. elegans lifespan or thought to promote mammalian health: 17α-estradiol, acarbose, green tea extract, nordihydroguaiaretic acid, and rapamycin. We found that green tea extract and nordihydroguaiaretic acid extend Caenorhabditis lifespan in a species-specific manner. Additionally, these two antioxidants conferred assay-specific effects in some studies—for example, decreasing survival for certain genetic backgrounds in manual survival assays in contrast with extended lifespan as assayed using automated C. elegans Lifespan Machines. We also observed that GTE and NDGA impact on older adult mobility capacity is dependent on genetic background, and that GTE reduces oxidative stress resistance in some Caenorhabditis strains. Overall, our analysis of the five compounds supports the general idea that genetic background and assay type can influence lifespan and health effects of compounds, and underscores that lifespan and health can be uncoupled by chemical interventions.

Monitoring population-level foraging distribution of a marine migratory species from land: strengths and weaknesses of the isotopic approach on the Northwest Atlantic loggerhead turtle aggregation - Simona A. Ceriani; Susan Murasko; David S. Addison; David Anderson; Greg Curry; Nicole A. Desjardin; Scott F. Eastman; Daniel R. Evans; Nancy Evou; Mariana M. P. B. Fuentes; Matthew H. Godfrey; Kristen M. Hart; et al. (Frontiers in Marine Science, 2023)
Assessing the linkage between breeding and non-breeding areas has important implications for understanding the fundamental biology of and conserving animal species. This is a challenging task for marine species, and in sea turtles a combination of stable isotope analysis (SIA) and satellite telemetry has been increasingly used. The Northwest Atlantic (NWA) loggerhead ( Caretta caretta ) Regional Management Unit, one of the largest sea turtle populations in the world, provides an excellent opportunity to investigate key biological patterns as well as methodological aspects related to the use of stable isotopes to infer spatial distribution of turtles in foraging areas. We provide the first comprehensive assessment of the annual distribution of NWA adult female loggerheads among foraging areas and investigate the efficacy of various analytical approaches as well as the effect of sample size in these types of studies. A total of 5168 individual females were sampled from seven Management Units (MUs) between 2013-2018. We provide the first estimate of the proportion of females originating from each MU that uses each foraging area and show how this proportion varies over time. We also estimate the relative importance (in terms of number of turtles) of each foraging area to the overall loggerhead breeding aggregation nesting in Florida and in the NWA for each year of the study. The foraging area used by reproductively active females differs considerably across MUs. One of these, the Subtropical NWA, is by far the most important foraging area in terms of both number of individuals and genetic diversity, and therefore this region may be considered as a conservation priority. Through simulations, we show that limited sizes of sample groups (unknowns; training; priors) may result in false geographic differentiation and consequently mislead interpretations. We provide thresholds and methodological recommendations for future studies. This study establishes a fundamental baseline for monitoring the annual contribution of foraging area to a terrestrial-based breeding aggregation of a marine animal in a cost-effective way. This type of monitoring allows for early detection of changes in foraging distributions—a possible effect of climate change on marine ecosystems or of area-specific anthropogenic threats.

Antibody Fc-binding profiles and ACE2 affinity to SARS-CoV-2 RBD variants - Ebene R. Haycroft; Samantha K. Davis; Pradhipa Ramanathan; Ester Lopez; Ruth A. Purcell; Li Lynn Tan; Phillip Pymm; Bruce D. Wines; P. Mark Hogarth; Adam K. Wheatley; Jennifer A. Juno; Samuel J. Redmond; et al. (Medical Microbiology and Immunology, 2023)
Emerging SARS-CoV-2 variants, notably Omicron, continue to remain a formidable challenge to worldwide public health. The SARS-CoV-2 receptor-binding domain (RBD) is a hotspot for mutations, reflecting its critical role at the ACE2 interface during viral entry. Here, we comprehensively investigated the impact of RBD mutations, including 5 variants of concern (VOC) or interest—including Omicron (BA.2)—and 33 common point mutations, both on IgG recognition and ACE2-binding inhibition, as well as FcγRIIa- and FcγRIIIa-binding antibodies, in plasma from two-dose BNT162b2-vaccine recipients and mild-COVID-19 convalescent subjects obtained during the first wave using a custom-designed bead-based 39-plex array. IgG-recognition and FcγR-binding antibodies were decreased against the RBD of Beta and Omicron, as well as point mutation G446S, found in several Omicron sub-variants as compared to wild type. Notably, while there was a profound decrease in ACE2 inhibition against Omicron, FcγR-binding antibodies were less affected, suggesting that Fc functional antibody responses may be better retained against the RBD of Omicron in comparison to neutralization. Furthermore, while measurement of RBD–ACE2-binding affinity via biolayer interferometry showed that all VOC RBDs have enhanced affinity to human ACE2, we demonstrate that human ACE2 polymorphisms, E35K (rs1348114695) has reduced affinity to VOCs, while K26R (rs4646116) and S19P (rs73635825) have increased binding kinetics to the RBD of VOCs, potentially affecting virus–host interaction and, thereby, host susceptibility. Collectively, our findings provide in-depth coverage of the impact of RBD mutations on key facets of host–virus interactions.

Experimental nutrient enrichment of forest streams reduces ecosystem nitrogen and phosphorus storage - Phillip M. Bumpers; Amy D. Rosemond; David W. P. Manning; John S. Kominoski; Jonathan P. Benstead; Lee M. Demi (Limnology and Oceanography, 2023)
Streams store nutrients in standing stocks of organic matter (OM) and associated biologically sequestered elements. Unlike standing stocks of autotrophs, detritus is depleted by nutrient enrichment, potentially reducing areal storage of detritus‐associated nutrients. To test effects of nutrient‐loading on storage of nitrogen (N) and phosphorus (P) by autotrophic and detrital‐pool compartments, we quantified the effects of 2 yr of continuous experimental N and P additions on fine benthic organic matter (FBOM), leaves, wood, and biofilms in five forest streams. Our design tested the relative strength of N vs. P on OM nutrient content, areal OM storage, and areal nutrient storage in OM types. Enrichment increased nutrient content of all OM types; %P increased more than %N in leaves, wood, and biofilms, but not FBOM. Biofilm %P and %N increased more than in all detrital types. Areal FBOM and leaf storage declined with nutrient enrichment. Biofilm standing stocks were generally higher with enrichment but were not related to the streamwater N and P gradients. Despite increased OM nutrient content, total areal nutrient storage in leaves and wood decreased due to reduced OM storage. Although annual nutrient storage was stabilized by FBOM, seasonal variation in nutrient storage increased with enrichment. Leaf‐associated nutrient storage was reduced in most seasons, whereas FBOM and biofilm nutrient storage increased in winter and spring, respectively, relative to pretreatment. Overall, the combined responses of all OM types to enrichment resulted in reduced storage and altered seasonal availability of carbon and nutrients, which has implications for consumers and downstream processes.

Autumn outmigrants in brown trout ( Salmo trutta ) are not a demographic dead‐end - Robert Wynne; Joshka Kaufmann; Jamie Coughlan; Karl. P. Phillips; Catherine Waters; Ross W. Finlay; Ger Rogan; Russell Poole; Philip McGinnity; Thomas E. Reed (Journal of Fish Biology, 2023)
Genetic identity analysis and PIT (passive integrated transponder) tagging were used to examine the freshwater return rates and phenotypic characteristics of n = 1791 downstream migrating juvenile Salmo trutta in the Burrishoole catchment (northwest Ireland) across the period September 2017 to December 2020. In this system, juveniles out‐migrate (move from freshwater into brackish or marine habitats) in every month of the year, with distinct seasonal peaks in spring (March through June; mostly silvered smolts) and autumn (September through December; mostly younger, unsilvered fry or parr). Both types exhibited a sex‐bias towards females, which was stronger in spring (78% females) than in autumn outmigrants (67%). Sixty‐nine returning fish were matched back to previous juvenile outmigrants, and similar return rates were found for spring outmigrants (5.0%), autumn outmigrants (3.3%) and fish that out‐migrated outside of spring or autumn (2.8%). Spring and autumn outmigrants returned at similar dates (typically mid to late July), but autumn fish were away for longer periods (median = 612 days; spring outmigrants = 104 days). Autumn outmigrants were 25% smaller than spring outmigrants at outmigration and 6% smaller on their return, and within both groups smaller/younger outmigrants spent longer away than larger/older outmigrants. Autumn outmigrants were more likely to return unsilvered as “slob” trout (84%) than spring outmigrants (31%), suggesting they make greater use of brackish habitats that might be safer, but less productive, than fully marine habitats. Nonetheless, both types also produced silvered “sea trout” (≥1+ sea‐age), implying neither is locked into a single life‐history strategy. The findings emphasise that autumn outmigrants and the transitional habitats that support their persistence should not be overlooked in salmonid management and conservation.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Optimization and Scale Up of Spray Dried CPZEN-45 Aerosol Powders for Inhaled Tuberculosis Treatment - Ian E. Stewart; Phillip G. Durham; Jacob M. Sittenauer; Aranza P. Barreda; Grayson W. Stowell; Carmella Moody; Jeffery B. Mecham; Catherine Simpson; Sharon Daily; Sara E. Maloney; Mark D. Williams; Diana Severynse-Stevens; et al. (Pharmaceutical Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Tropical tree growth sensitivity to climate is driven by species intrinsic growth rate and leaf traits - David Bauman; Claire Fortunel; Lucas A. Cernusak; Lisa P. Bentley; Sean M. McMahon; Sami W. Rifai; Jesús Aguirre‐Gutiérrez; Imma Oliveras; Matt Bradford; Susan G. W. Laurance; Guillaume Delhaye; Michael F. Hutchinson; et al. (Global Change Biology, 2022)
A better understanding of how climate affects growth in tree species is essential for improved predictions of forest dynamics under climate change. Long‐term climate averages (mean climate) drive spatial variations in species’ baseline growth rates, whereas deviations from these averages over time (anomalies) can create growth variation around the local baseline. However, the rarity of long‐term tree census data spanning climatic gradients has so far limited our understanding of their respective role, especially in tropical systems. Furthermore, tree growth sensitivity to climate is likely to vary widely among species, and the ecological strategies underlying these differences remain poorly understood. Here, we utilize an exceptional dataset of 49 years of growth data for 509 tree species across 23 tropical rainforest plots along a climatic gradient to examine how multiannual tree growth responds to both climate means and anomalies, and how species’ functional traits mediate these growth responses to climate. We show that anomalous increases in atmospheric evaporative demand and solar radiation consistently reduced tree growth. Drier forests and fast‐growing species were more sensitive to water stress anomalies. In addition, species traits related to water use and photosynthesis partly explained differences in growth sensitivity to both climate means and anomalies. Our study demonstrates that both climate means and anomalies shape tree growth in tropical forests and that species traits can provide insights into understanding these demographic responses to climate change, offering a promising way forward to forecast tropical forest dynamics under different climate trajectories.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Genomic‐based epidemiology reveals independent origins and gene flow of glyphosate resistance in Bassia scoparia populations across North America - Karl Ravet; Crystal D. Sparks; Andrea L. Dixon; Anita Küpper; Eric P. Westra; Dean J. Pettinga; Patrick J. Tranel; Joel Felix; Don W. Morishita; Prashant Jha; Andrew Kniss; Phillip W. Stahlman; et al. (Molecular Ecology, 2021)
Genomic‐based epidemiology can provide insight into the origins and spread of herbicide resistance mechanisms in weeds. We used kochia ( Bassia scoparia ) populations resistant to the herbicide glyphosate from across western North America to test the alternative hypotheses that (i) a single EPSPS gene duplication event occurred initially in the Central Great Plains and then subsequently spread to all other geographical areas now exhibiting glyphosate‐resistant kochia populations or that (ii) gene duplication occurred multiple times in independent events in a case of parallel evolution. We used qPCR markers previously developed for measuring the structure of the EPSPS tandem duplication to investigate whether all glyphosate‐resistant individuals had the same EPSPS repeat structure. We also investigated population structure using simple sequence repeat markers to determine the relatedness of kochia populations from across the Central Great Plains, Northern Plains and the Pacific Northwest. We found that the original EPSPS duplication genotype was predominant in the Central Great Plains where glyphosate resistance was first reported. We identified two additional EPSPS duplication genotypes, one having geographical associations with the Northern Plains and the other with the Pacific Northwest. The EPSPS duplication genotype from the Pacific Northwest seems likely to represent a second, independent evolutionary origin of a resistance allele. We found evidence of gene flow across populations and a general lack of population structure. The results support at least two independent evolutionary origins of glyphosate resistance in kochia, followed by substantial and mostly geographically localized gene flow to spread the resistance alleles into diverse genetic backgrounds.

Nitrogen and phosphorus cycling in an ombrotrophic peatland: a benchmark for assessing change - Verity G. Salmon; Deanne J. Brice; Scott Bridgham; Joanne Childs; Jake Graham; Natalie A. Griffiths; Kirsten Hofmockel; Colleen M. Iversen; Terri M. Jicha; Randy K. Kolka; Joel E. Kostka; Avni Malhotra; et al. (Plant and Soil, 2021)

Non-native brittle star interactions with native octocoral epizoites: an endemic benthic ctenophore in peril? - Peter W. Glynn; Brian Coffman; Kyle Dettloff; Joshua Dominguez; Phillip R. Gillette; Nicholas Martinez; Nicholas P. Jones; Bernhard M. Riegl (Marine Biology, 2021)

An unusually diverse genus of Collembola in the Cape Floristic Region characterised by substantial desiccation tolerance - W. P. Amy Liu; Laura M. Phillips; John S. Terblanche; Charlene Janion-Scheepers; Steven L. Chown (Oecologia, 2021)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Interaction of Fertilizer Phosphorus Rate and Placement/Timing on Potatoes - Keith A. Kelling; Richard P. Wolkowski; Phillip E. Speth; Todd W. Andraski (American Journal of Potato Research, 2020)

Cohort antler size signals environmental stress in a moderate climate - Bronson K. Strickland; P. Grady Dixon; Phillip D. Jones; Stephen Demarais; Nathan O. Owen; David A. Cox; Katie Landry-Guyton; W. Mark Baldwin; William T. McKinley (International Journal of Biometeorology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Nocturnal reductions in body temperature in high-elevation Neotropical birds - Keith Burnett; Matthew N. Zipple; Lauren T. Phillips; Pooja Panwar; Liam P. Mcguire; W. Alice Boyle (Tropical Ecology, 2019)

Automated lifespan determination across Caenorhabditis strains and species reveals assay-specific effects of chemical interventions - Stephen A. Banse; Mark Lucanic; Christine A. Sedore; Anna L. Coleman-Hulbert; W. Todd Plummer; Esteban Chen; Jason L. Kish; David Hall; Brian Onken; Michael P. Presley; E. Grace Jones; Benjamin W. Blue; et al. (GeroScience, 2019)
The goal of the Caenorhabditis Intervention Testing Program is to identify robust and reproducible pro-longevity interventions that are efficacious across genetically diverse cohorts in the Caenorhabditis genus. The project design features multiple experimental replicates collected by three different laboratories. Our initial effort employed fully manual survival assays. With an interest in increasing throughput, we explored automation with flatbed scanner-based Automated Lifespan Machines (ALMs). We used ALMs to measure survivorship of 22 Caenorhabditis strains spanning three species. Additionally, we tested five chemicals that we previously found extended lifespan in manual assays. Overall, we found similar sources of variation among trials for the ALM and our previous manual assays, verifying reproducibility of outcome. Survival assessment was generally consistent between the manual and the ALM assays, although we did observe radically contrasting results for certain compound interventions. We found that particular lifespan outcome differences could be attributed to protocol elements such as enhanced light exposure of specific compounds in the ALM, underscoring that differences in technical details can influence outcomes and therefore interpretation. Overall, we demonstrate that the ALMs effectively reproduce a large, conventionally scored dataset from a diverse test set, independently validating ALMs as a robust and reproducible approach toward aging-intervention screening.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

The Importance of Consistent Global Forest Aboveground Biomass Product Validation - L. Duncanson; J. Armston; M. Disney; V. Avitabile; N. Barbier; K. Calders; S. Carter; J. Chave; M. Herold; T. W. Crowther; M. Falkowski; J. R. Kellner; et al. (Surveys in Geophysics, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Dominant tree species drive beta diversity patterns in western Amazonia - Frederick C. Draper; Gregory P. Asner; Eurídice N. Honorio Coronado; Timothy R. Baker; Roosevelt García‐Villacorta; Nigel C. A. Pitman; Paul V. A. Fine; Oliver L. Phillips; Ricardo Zárate Gómez; Carlos A. Amasifuén Guerra; Manuel Flores Arévalo; Rodolfo Vásquez Martínez; et al. (Ecology, 2019)
The forests of western Amazonia are among the most diverse tree communities on Earth, yet this exceptional diversity is distributed highly unevenly within and among communities. In particular, a small number of dominant species account for the majority of individuals, whereas the large majority of species are locally and regionally extremely scarce. By definition, dominant species contribute little to local species richness (alpha diversity), yet the importance of dominant species in structuring patterns of spatial floristic turnover (beta diversity) has not been investigated. Here, using a network of 207 forest inventory plots, we explore the role of dominant species in determining regional patterns of beta diversity (community‐level floristic turnover and distance‐decay relationships) across a range of habitat types in northern lowland Peru. Of the 2,031 recorded species in our data set, only 99 of them accounted for 50% of individuals. Using these 99 species, it was possible to reconstruct the overall features of regional beta diversity patterns, including the location and dispersion of habitat types in multivariate space, and distance‐decay relationships. In fact, our analysis demonstrated that regional patterns of beta diversity were better maintained by the 99 dominant species than by the 1,932 others, whether quantified using species‐abundance data or species presence–absence data. Our results reveal that dominant species are normally common only in a single forest type. Therefore, dominant species play a key role in structuring western Amazonian tree communities, which in turn has important implications, both practically for designing effective protected areas, and more generally for understanding the determinants of beta diversity patterns.

Host‐derived population genomics data provides insights into bacterial and diatom composition of the killer whale skin - Rebecca Hooper; Jaelle C. Brealey; Tom van der Valk; Antton Alberdi; John W. Durban; Holly Fearnbach; Kelly M. Robertson; Robin W. Baird; M. Bradley Hanson; Paul Wade; M. Thomas P. Gilbert; Phillip A. Morin; et al. (Molecular Ecology, 2019)
Recent exploration into the interactions and relationship between hosts and their microbiota has revealed a connection between many aspects of the host's biology, health and associated micro‐organisms. Whereas amplicon sequencing has traditionally been used to characterize the microbiome, the increasing number of published population genomics data sets offers an underexploited opportunity to study microbial profiles from the host shotgun sequencing data. Here, we use sequence data originally generated from killer whale Orcinus orca skin biopsies for population genomics, to characterize the skin microbiome and investigate how host social and geographical factors influence the microbial community composition. Having identified 845 microbial taxa from 2.4 million reads that did not map to the killer whale reference genome, we found that both ecotypic and geographical factors influence community composition of killer whale skin microbiomes. Furthermore, we uncovered key taxa that drive the microbiome community composition and showed that they are embedded in unique networks, one of which is tentatively linked to diatom presence and poor skin condition. Community composition differed between Antarctic killer whales with and without diatom coverage, suggesting that the previously reported episodic migrations of Antarctic killer whales to warmer waters associated with skin turnover may control the effects of potentially pathogenic bacteria such as Tenacibaculum dicentrarchi . Our work demonstrates the feasibility of microbiome studies from host shotgun sequencing data and highlights the importance of metagenomics in understanding the relationship between host and microbial ecology.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Remotely sensed canopy nitrogen correlates with nitrous oxide emissions in a lowland tropical rainforest - Fiona M. Soper; Benjamin W. Sullivan; Megan K. Nasto; Brooke B. Osborne; David Bru; Christopher S. Balzotti; Phillip G. Taylor; Gregory P. Asner; Alan R. Townsend; Laurent Philippot; Stephen Porder; Cory C. Cleveland (Ecology, 2018)
Tropical forests exhibit significant heterogeneity in plant functional and chemical traits that may contribute to spatial patterns of key soil biogeochemical processes, such as carbon storage and greenhouse gas emissions. Although tropical forests are the largest ecosystem source of nitrous oxide (N 2 O), drivers of spatial patterns within forests are poorly resolved. Here, we show that local variation in canopy foliar N, mapped by remote‐sensing image spectroscopy, correlates with patterns of soil N 2 O emission from a lowland tropical rainforest. We identified ten 0.25 ha plots (assemblages of 40–70 individual trees) in which average remotely‐sensed canopy N fell above or below the regional mean. The plots were located on a single minimally‐dissected terrace ( 2 ) where soil type, vegetation structure and climatic conditions were relatively constant. We measured N 2 O fluxes monthly for 1 yr and found that high canopy N species assemblages had on average three‐fold higher total mean N 2 O fluxes than nearby lower canopy N areas. These differences are consistent with strong differences in litter stoichiometry, nitrification rates and soil nitrate concentrations. Canopy N status was also associated with microbial community characteristics: lower canopy N plots had two‐fold greater soil fungal to bacterial ratios and a significantly lower abundance of ammonia‐oxidizing archaea, although genes associated with denitrification ( nirS, nirK, nosZ ) showed no relationship with N 2 O flux. Overall, landscape emissions from this ecosystem are at the lowest end of the spectrum reported for tropical forests, consist with multiple metrics indicating that these highly productive forests retain N tightly and have low plant‐available losses. These data point to connections between canopy and soil processes that have largely been overlooked as a driver of denitrification. Defining relationships between remotely‐sensed plant traits and soil processes offers the chance to map these processes at large scales, potentially increasing our ability to predict N 2 O emissions in heterogeneous landscapes.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Route Fidelity during Marine Megafauna Migration - Travis W. Horton; Nan Hauser; Alexandre N. Zerbini; Malcolm P. Francis; Michael L. Domeier; Artur Andriolo; Daniel P. Costa; Patrick W. Robinson; Clinton A. J. Duffy; Nicole Nasby-Lucas; Richard N. Holdaway; Phillip J. Clapham (Frontiers in Marine Science, 2017)

Elevated rate of alcohol consumption in borderline personality disorder patients in daily life - Ryan W. Carpenter; Constantine J. Trela; Sean P. Lane; Phillip K. Wood; Thomas M. Piasecki; Timothy J. Trull (Psychopharmacology, 2017)

Faster turnover of new soil carbon inputs under increased atmospheric CO 2 - Kees Jan van Groenigen; Craig W. Osenberg; César Terrer; Yolima Carrillo; Feike A. Dijkstra; James Heath; Ming Nie; Elise Pendall; Richard P. Phillips; Bruce A. Hungate (Global Change Biology, 2017)
Rising levels of atmospheric CO 2 frequently stimulate plant inputs to soil, but the consequences of these changes for soil carbon (C) dynamics are poorly understood. Plant‐derived inputs can accumulate in the soil and become part of the soil C pool (“new soil C”), or accelerate losses of pre‐existing (“old”) soil C. The dynamics of the new and old pools will likely differ and alter the long‐term fate of soil C, but these separate pools, which can be distinguished through isotopic labeling, have not been considered in past syntheses. Using meta‐analysis, we found that while elevated CO 2 (ranging from 550 to 800 parts per million by volume) stimulates the accumulation of new soil C in the short term ( CO 2 does not affect the decomposition or the size of the old soil C pool over either temporal scale. Our results are inconsistent with predictions of conventional soil C models and suggest that elevated CO 2 might increase turnover rates of new soil C. Because increased turnover rates of new soil C limit the potential for additional soil C sequestration, the capacity of land ecosystems to slow the rise in atmospheric CO 2 concentrations may be smaller than previously assumed.

Pushing precipitation to the extremes in distributed experiments: recommendations for simulating wet and dry years - Alan K. Knapp; Meghan L. Avolio; Claus Beier; Charles J. W. Carroll; Scott L. Collins; Jeffrey S. Dukes; Lauchlan H. Fraser; Robert J. Griffin‐Nolan; David L. Hoover; Anke Jentsch; Michael E. Loik; Richard P. Phillips; et al. (Global Change Biology, 2017)
Intensification of the global hydrological cycle, ranging from larger individual precipitation events to more extreme multiyear droughts, has the potential to cause widespread alterations in ecosystem structure and function. With evidence that the incidence of extreme precipitation years (defined statistically from historical precipitation records) is increasing, there is a clear need to identify ecosystems that are most vulnerable to these changes and understand why some ecosystems are more sensitive to extremes than others. To date, opportunistic studies of naturally occurring extreme precipitation years, combined with results from a relatively small number of experiments, have provided limited mechanistic understanding of differences in ecosystem sensitivity, suggesting that new approaches are needed. Coordinated distributed experiments ( CDE s) arrayed across multiple ecosystem types and focused on water can enhance our understanding of differential ecosystem sensitivity to precipitation extremes, but there are many design challenges to overcome (e.g., cost, comparability, standardization). Here, we evaluate contemporary experimental approaches for manipulating precipitation under field conditions to inform the design of ‘Drought‐Net’, a relatively low‐cost CDE that simulates extreme precipitation years. A common method for imposing both dry and wet years is to alter each ambient precipitation event. We endorse this approach for imposing extreme precipitation years because it simultaneously alters other precipitation characteristics (i.e., event size) consistent with natural precipitation patterns. However, we do not advocate applying identical treatment levels at all sites – a common approach to standardization in CDE s. This is because precipitation variability varies >fivefold globally resulting in a wide range of ecosystem‐specific thresholds for defining extreme precipitation years. For CDE s focused on precipitation extremes, treatments should be based on each site's past climatic characteristics. This approach, though not often used by ecologists, allows ecological responses to be directly compared across disparate ecosystems and climates, facilitating process‐level understanding of ecosystem sensitivity to precipitation extremes.

Genetic structure of the beaked whale genus Berardius in the North Pacific, with genetic evidence for a new species - Phillip A. Morin; C. Scott Baker; Reid S. Brewer; Alexander M. Burdin; Merel L. Dalebout; James P. Dines; Ivan Fedutin; Olga Filatova; Erich Hoyt; Jean‐Luc Jung; Morgane Lauf; Charles W. Potter; et al. (Marine Mammal Science, 2017)
There are two recognized species in the genus Berardius , Baird's and Arnoux's beaked whales. In Japan, whalers have traditionally recognized two forms of Baird's beaked whales, the common “slate‐gray” form and a smaller, rare “black” form. Previous comparison of mt DNA control region sequences from three black specimens to gray specimens around Japan indicated that the two forms comprise different stocks and potentially different species. We have expanded sampling to include control region haplotypes of 178 Baird's beaked whales from across their range in the North Pacific. We identified five additional specimens of the black form from the Aleutian Islands and Bering Sea, for a total of eight “black” specimens. The divergence between mt DNA haplotypes of the black and gray forms of Baird's beaked whale was greater than their divergence from the congeneric Arnoux's beaked whale found in the Southern Ocean, and similar to that observed among other congeneric beaked whale species. Taken together, genetic evidence from specimens in Japan and across the North Pacific, combined with evidence of smaller adult body size, indicate presence of an unnamed species of Berardius in the North Pacific.

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Tree‐mycorrhizal associations detected remotely from canopy spectral properties - Joshua B. Fisher; Sean Sweeney; Edward R. Brzostek; Tom P. Evans; Daniel J. Johnson; Jonathan A. Myers; Norman A. Bourg; Amy T. Wolf; Robert W. Howe; Richard P. Phillips (Global Change Biology, 2016)
A central challenge in global ecology is the identification of key functional processes in ecosystems that scale, but do not require, data for individual species across landscapes. Given that nearly all tree species form symbiotic relationships with one of two types of mycorrhizal fungi – arbuscular mycorrhizal ( AM ) and ectomycorrhizal ( ECM ) fungi – and that AM ‐ and ECM ‐dominated forests often have distinct nutrient economies, the detection and mapping of mycorrhizae over large areas could provide valuable insights about fundamental ecosystem processes such as nutrient cycling, species interactions, and overall forest productivity. We explored remotely sensed tree canopy spectral properties to detect underlying mycorrhizal association across a gradient of AM ‐ and ECM ‐dominated forest plots. Statistical mining of reflectance and reflectance derivatives across moderate/high‐resolution Landsat data revealed distinctly unique phenological signals that differentiated AM and ECM associations. This approach was trained and validated against measurements of tree species and mycorrhizal association across ~130 000 trees throughout the temperate United States. We were able to predict 77% of the variation in mycorrhizal association distribution within the forest plots ( P

The impact of p53 on DNA damage and metabolic activation of the environmental carcinogen benzo[a]pyrene: effects in Trp53(+/+), Trp53(+/–) and Trp53(−/−) mice - Annette M. Krais; Ewoud N. Speksnijder; Joost P. M. Melis; Radek Indra; Michaela Moserova; Roger W. Godschalk; Frederik-J. van Schooten; Albrecht Seidel; Klaus Kopka; Heinz H. Schmeiser; Marie Stiborova; David H. Phillips; et al. (Archives of Toxicology, 2016)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

Geographic and temporal dynamics of a global radiation and diversification in the killer whale - Phillip A. Morin; Kim M. Parsons; Frederick I. Archer; María C. Ávila‐Arcos; Lance G. Barrett‐Lennard; Luciano Dalla Rosa; Sebastián Duchêne; John W. Durban; Graeme M. Ellis; Steven H. Ferguson; John K. Ford; Michael J. Ford; et al. (Molecular Ecology, 2015)
Global climate change during the Late Pleistocene periodically encroached and then released habitat during the glacial cycles, causing range expansions and contractions in some species. These dynamics have played a major role in geographic radiations, diversification and speciation. We investigate these dynamics in the most widely distributed of marine mammals, the killer whale ( Orcinus orca ), using a global data set of over 450 samples. This marine top predator inhabits coastal and pelagic ecosystems ranging from the ice edge to the tropics, often exhibiting ecological, behavioural and morphological variation suggestive of local adaptation accompanied by reproductive isolation. Results suggest a rapid global radiation occurred over the last 350 000 years. Based on habitat models, we estimated there was only a 15% global contraction of core suitable habitat during the last glacial maximum, and the resources appeared to sustain a constant global effective female population size throughout the Late Pleistocene. Reconstruction of the ancestral phylogeography highlighted the high mobility of this species, identifying 22 strongly supported long‐range dispersal events including interoceanic and interhemispheric movement. Despite this propensity for geographic dispersal, the increased sampling of this study uncovered very few potential examples of ancestral dispersal among ecotypes. Concordance of nuclear and mitochondrial data further confirms genetic cohesiveness, with little or no current gene flow among sympatric ecotypes. Taken as a whole, our data suggest that the glacial cycles influenced local populations in different ways, with no clear global pattern, but with secondary contact among lineages following long‐range dispersal as a potential mechanism driving ecological diversification.

The effect of impedance to root growth on plant architecture in wheat - Kemo Jin; Jianbo Shen; Rhys W. Ashton; Rodger P. White; Ian C. Dodd; Andrew L. Phillips; Martin A. J. Parry; William R. Whalley (Plant and Soil, 2015)

Associations of prostate cancer risk variants with disease aggressiveness: results of the NCI-SPORE Genetics Working Group analysis of 18,343 cases - Brian T. Helfand; Kimberly A. Roehl; Phillip R. Cooper; Barry B. McGuire; Liesel M. Fitzgerald; Geraldine Cancel-Tassin; Jean-Nicolas Cornu; Scott Bauer; Erin L. Van Blarigan; Xin Chen; David Duggan; Elaine A. Ostrander; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Use of Hygiene Protocols to Control the Spread of Viruses in a Hotel - Laura Y. Sifuentes; David W. Koenig; Ronnie L. Phillips; Kelly A. Reynolds; Charles P. Gerba (Food and Environmental Virology, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Fast demographic traits promote high diversification rates of Amazonian trees - Timothy R. Baker; R. Toby Pennington; Susana Magallon; Emanuel Gloor; William F. Laurance; Miguel Alexiades; Esteban Alvarez; Alejandro Araujo; Eric J. M. M. Arets; Gerardo Aymard; Atila Alves de Oliveira; Iêda Amaral; et al. (Ecology Letters, 2014)
The Amazon rain forest sustains the world's highest tree diversity, but it remains unclear why some clades of trees are hyperdiverse, whereas others are not. Using dated phylogenies, estimates of current species richness and trait and demographic data from a large network of forest plots, we show that fast demographic traits – short turnover times – are associated with high diversification rates across 51 clades of canopy trees. This relationship is robust to assuming that diversification rates are either constant or decline over time, and occurs in a wide range of Neotropical tree lineages. This finding reveals the crucial role of intrinsic, ecological variation among clades for understanding the origin of the remarkable diversity of Amazonian trees and forests.

Mitogenomic insights into a recently described and rarely observed killer whale morphotype - Andrew D. Foote; Phillip A. Morin; Robert L. Pitman; María C. Ávila-Arcos; John W. Durban; Anton van Helden; Mikkel-Holger S. Sinding; M. Thomas P. Gilbert (Polar Biology, 2013)

Integration, stability and expression of the E. coli phytase transgene in the Cassie line of Yorkshire Enviropig™ - Cecil W. Forsberg; Roy G. Meidinger; Mingfu Liu; Michael Cottrill; Serguei Golovan; John P. Phillips (Transgenic Research, 2013)

Genotypic variation in the ability of wheat roots to penetrate wax layers - W. R. Whalley; I. C. Dodd; C. W. Watts; C. P. Webster; A. L. Phillips; J. Andralojc; R. P. White; W. J. Davies; M. A. J. Parry (Plant and Soil, 2013)

Study of transforming growth factor alpha for the maintenance of human embryonic stem cells - Andy C. H. Chen; Y. L. Lee; Denise Y. C. Hou; S. W. Fong; Qian Peng; Ronald T. K. Pang; Phillip C. N. Chiu; P. C. Ho; Kai-Fai Lee; William S. B. Yeung (Cell and Tissue Research, 2012)

Variable nitrogen rate determination from plant spectral reflectance in soft red winter wheat - W. E. Thomason; S. B. Phillips; P. H. Davis; J. G. Warren; M. M. Alley; M. S. Reiter (Precision Agriculture, 2011)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Linkage to chromosome 2q32.2-q33.3 in familial serrated neoplasia (Jass syndrome) - Aedan Roberts; Derek Nancarrow; Mark Clendenning; Daniel D. Buchanan; Mark A. Jenkins; David Duggan; Darin Taverna; Diane McKeone; Rhiannon Walters; Michael D. Walsh; Bruce W. Young; Jeremy R. Jass; et al. (Familial Cancer, 2011)

High mangrove density enhances surface accretion, surface elevation change, and tree survival in coastal areas susceptible to sea-level rise - M. P. Kumara; L. P. Jayatissa; K. W. Krauss; D. H. Phillips; M. Huxham (Oecologia, 2010)

Intercomparison and analyses of the climatology of the West African Monsoon in the West African Monsoon Modeling and Evaluation project (WAMME) first model intercomparison experiment - Yongkang Xue; Fernando De Sales; W. K.-M. Lau; Aaron Boone; Jinming Feng; Paul Dirmeyer; Zhichang Guo; Kyu-Myong Kim; Akio Kitoh; Vadlamani Kumar; Isabelle Poccard-Leclercq; Natalie Mahowald; et al. (Climate Dynamics, 2010)

Does the disturbance hypothesis explain the biomass increase in basin‐wide Amazon forest plot data? - M. GLOOR; O. L. PHILLIPS; J. J. LLOYD; S. L. LEWIS; Y. MALHI; T. R. BAKER; G. LÓPEZ‐GONZALEZ; J. PEACOCK; S. ALMEIDA; A. C. ALVES De OLIVEIRA; E. ALVAREZ; I. AMARAL; et al. (Global Change Biology, 2009)
Positive aboveground biomass trends have been reported from old‐growth forests across the Amazon basin and hypothesized to reflect a large‐scale response to exterior forcing. The result could, however, be an artefact due to a sampling bias induced by the nature of forest growth dynamics. Here, we characterize statistically the disturbance process in Amazon old‐growth forests as recorded in 135 forest plots of the RAINFOR network up to 2006, and other independent research programmes, and explore the consequences of sampling artefacts using a data‐based stochastic simulator. Over the observed range of annual aboveground biomass losses, standard statistical tests show that the distribution of biomass losses through mortality follow an exponential or near‐identical Weibull probability distribution and not a power law as assumed by others. The simulator was parameterized using both an exponential disturbance probability distribution as well as a mixed exponential–power law distribution to account for potential large‐scale blowdown events. In both cases, sampling biases turn out to be too small to explain the gains detected by the extended RAINFOR plot network. This result lends further support to the notion that currently observed biomass gains for intact forests across the Amazon are actually occurring over large scales at the current time, presumably as a response to climate change.

Controls of Aboveground Net Primary Production in Mesic Savanna Grasslands: An Inter-Hemispheric Comparison - Greg M. Buis; John M. Blair; Deron E. Burkepile; Catherine E. Burns; Annikki J. Chamberlain; Phillip L. Chapman; Scott L. Collins; Richard W. S. Fynn; Navashni Govender; Kevin P. Kirkman; Melinda D. Smith; Alan K. Knapp (Ecosystems, 2009)

Aflatoxin–albumin adducts and correlation with decreased serum levels of vitamins A and E in an adult Ghanaian population - L. Tang; L. Xu; E. Afriyie-Gyawu; W. Liu; P. Wang; Y. Tang; Z. Wang; H.J. Huebner; N.-A. Ankrah; D. Ofori-Adjei; J.H. Williams; J.-S. Wang; et al. (Food Additives & Contaminants: Part A, 2009)

Differentiating salmon populations at broad and fine geographical scales with microsatellites and single nucleotide polymorphisms - S. R. NARUM; M. BANKS; T. D. BEACHAM; M. R. BELLINGER; M. R. CAMPBELL; J. DEKONING; A. ELZ; C. M. GUTHRIE III; C. KOZFKAY; K. M. MILLER; P. MORAN; R. PHILLIPS; et al. (Molecular Ecology, 2008)
Single nucleotide polymorphisms (SNPs) are appealing genetic markers due to several beneficial attributes, but uncertainty remains about how many of these bi‐allelic markers are necessary to have sufficient power to differentiate populations, a task now generally accomplished with highly polymorphic microsatellite markers. In this study, we tested the utility of 37 SNPs and 13 microsatellites for differentiating 29 broadly distributed populations of Chinook salmon ( n = 2783). Information content of all loci was determined by In and , and the top 12 markers ranked by In were microsatellites, but the 6 highest, and 7 of the top 10 ranked markers, were SNPs. The mean ratio of random SNPs to random microsatellites ranged from 3.9 to 4.1, but this ratio was consistently reduced when only the most informative loci were included. Individual assignment test accuracy was higher for microsatellites (73.1%) than SNPs (66.6%), and pooling all 50 markers provided the highest accuracy (83.2%). When marker types were combined, as few as 15 of the top ranked loci provided higher assignment accuracy than either microsatellites or SNPs alone. Neighbour‐joining dendrograms revealed similar clustering patterns and pairwise tests of population differentiation had nearly identical results with each suite of markers. Statistical tests and simulations indicated that closely related populations were better differentiated by microsatellites than SNPs. Our results indicate that both types of markers are likely to be useful in population genetics studies and that, in some cases, a combination of SNPs and microsatellites may be the most effective suite of loci.

Attenuation tomography of the Southern Apennines (Italy) - F. Zolezzi; P. Morasca; K. Mayeda; W. S. Phillips; C. Eva (Journal of Seismology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Nocturnal foraging by great skuas Stercorarius skua: implications for conservation of storm-petrel populations - Stephen C. Votier; Jonathan E. Crane; Stuart Bearhop; Ana de León; Claire A. McSorley; Eduardo Mínguez; Ian P. Mitchell; Matthew Parsons; Richard A. Phillips; Robert W. Furness (Journal of Ornithology, 2006)

Tolerance of Five West Coast Marine Toxicity Test Organisms to Ammonia - B. M. Phillips; P. A. Nicely; J. W. Hunt; B. S. Anderson; R. S. Tjeerdema; F. H. Palmer (Bulletin of Environmental Contamination and Toxicology, 2005)

Twentieth century north atlantic climate change. Part I: assessing determinism - J. W. Hurrell; M. P. Hoerling; A. S. Phillips; T. Xu (Climate Dynamics, 2004)

Twentieth century North Atlantic climate change. Part II: Understanding the effect of Indian Ocean warming - M. P. Hoerling; J. W. Hurrell; T. Xu; G. T. Bates; A. S. Phillips (Climate Dynamics, 2004)

A Comparison of In Situ and Laboratory Toxicity Tests with the Estuarine Amphipod Eohaustorius estuarius - B. S. Anderson; J. W. Hunt; B. M. Phillips; P. A. Nicely; R. S. Tjeerdema; M. Martin (Archives of Environmental Contamination and Toxicology, 2004)

Toxicity of Cadmium-Copper-Nickel-Zinc Mixtures to Larval Purple Sea Urchins ( Strongylocentrotus purpuratus ) - B. M. Phillips; P. A. Nicely; J. W. Hunt; B. S. Anderson; R. S. Tjeerdema; S. E. Palmer; F. H. Palmer; H. M. Puckett (Bulletin of Environmental Contamination and Toxicology, 2003)

High-resolution structural analysis of biolistic transgene integration into the genome of wheat - S. A. Jackson; P. Zhang; W. P. Chen; R. L. Phillips; B. Friebe; S. Muthukrishnan; B. S. Gill (Theoretical and Applied Genetics, 2001)

Effect of creatine supplementation on metabolism and performance in humans during intermittent sprint cycling - J. P. Finn; T. R. Ebert; R. T. Withers; M. F. Carey; M. Mackay; J. W. Phillips; M. A. Febbraio (European Journal of Applied Physiology, 2001)

Sampling and trapping to monitor insect populations in relation to CA and/or fumigation - D. Shuman; Nancy D. Epsky; B. Bridgeman; T.W Phillips; C. W. Doud; M. D. Toews; B. Subramanyam; P. W. Flinn; C. Reed; D. Hagstrum; P. Flinn; T. W. Phillips (Phytoparasitica, 2001)

Biological responses of arthropods to treatment with CA and/or fumigation - A. Carpenter; C. Downes; L. Hansen; M. Shelton; T. I. Ofuya; Ch. Reichmuth; C. Adler; M. Emekci; S. Navarro; J. E. Donahaye; Miriam Rindner; A. Azrieli; et al. (Phytoparasitica, 2001)

Physical and chemical processes in the application of CA and/or fumigation - Cecilia V. De Dios; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; D. D. Julian; I. V. Dator; R. L. Tiongson; J. van S. Graver; S. Pratt; C. Reed; Sylvia Allen; G. N. Mbata; T. W. Phillips; et al. (Phytoparasitica, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Protein targeting in the analysis of learning and memory: a potential alternative to gene targeting - R. Gerlai; Simon P. Williams; Belinda Cairns; Nicholas Van Bruggen; Paul Moran; A. Shih; Ingrid Caras; Hans Sauer; Heidi S. Phillips; John W. Winslow (Experimental Brain Research, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Establishment ofPhytoseiulus persimilis [Acari: Phytoseiidae] in Southern California - J. A. McMurtry; E. R. Oatman; P. A. Phillips; C. W. Wood (BioControl, 1978)

Sectional notes - H. G. Zuckerman; C. H. Metzger; W. B. Ward; C. L. Fitch; Julian C. Miller; Ralph W. Donaldson; A. G. Tolaas; Phillip A. Hoff; Dan O'Brien; E. V. Hardenburg; E. B. Tussing; S. P. Swenson (American Journal of Potato Research, 1936)